2009
DOI: 10.1159/000224794
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Type 2 Diabetes on Mortality in End-Stage Renal Disease Patients Differs between Genders

Abstract: Background/Aims: In diabetics with end-stage renal disease (ESRD), risk of death has been reported to be non-constant after the first dialysis, and different outcomes have been observed between genders. We assessed the impact of type 2 diabetes (T2DM) on mortality in dialysis regarding its differential effect by gender using time-dependent analyses. Methods: All T2DM and non-diabetic (no-DM) patients who started dialysis in two renal units in Lyon, France, between January 1, 1995, and December 31, 2007, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The cardiovascular complications of DM contribute to the higher mortalities observed for diabetic patients [ 15 ]. Of the patients in the present study, 44% had DM, a higher percentage than those reported in other studies (range of 9% [ 12 ] to 22% [ 13 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular complications of DM contribute to the higher mortalities observed for diabetic patients [ 15 ]. Of the patients in the present study, 44% had DM, a higher percentage than those reported in other studies (range of 9% [ 12 ] to 22% [ 13 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, population aging, inactivity, growing prevalence of obesity, and improved management of chronic complications have contributed to an epidemic of type 2 diabetes (T2DM) [4,18-23]. T2DM is particularly common among African Americans, Latinos, Native Americans, and Asian Americans/Pacific Islanders [24].…”
Section: Study Descriptionmentioning
confidence: 99%
“…Diabetic nephropathy affects about 10-20% of people with diabetes [31,32] and is a leading cause of ESRD [21-23,31]. Furthermore, studies have shown that individuals with both diabetes and ESRD have higher morbidity and mortality rates than individuals with only one of these conditions [4,33,34]. Finally, it has also been reported that women with ESRD have worse outcomes compared to men [4,28,29].…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation has been that the death rates of some wait-listed subgroups (e.g. patients with peripheral vascular disease or diabetes [13,14]) increase with time on dialysis, whereas transplantation would lengthen their survival [15]. Although some survival studies of wait-listed dialysis patients versus kidney transplant recipients have expressed their results in projected years of life gained [5] or long-term hazard ratios for death [5,6], assessment of current graft allocation policies requires a comparison of the death rates according to ESRD duration.…”
Section: Introductionmentioning
confidence: 99%